Efeitos de plantas de cobertura em atributos químicos do solo - Bettiol, Aline Carla Trombeta [UNESP] (2015)
Cover crops before crop season can influence soil chemical attributes, it may reduce the amount of nutrients to be provide to the crop. Therefore, the aimed of this study was to evaluate the effects of cover crops on soil chemical attributes after twelve years of cultivation in corn pre-cropping. The experiment was conducted at Unesp Jaboticabal-SP, Brasil, in a red Oxisol, clayey. The experimental design was made in a randomized block, split plot with four replications. The main treatments were cover crops: sunn hemp, jack bean, lablab, millet, velvet bean gray and spontaneous vegetation. The secondary treatments were the depths of soil sampling. Soil samples were collected at the beginning of the 2012/2013 harvest, 29 days after sowing of maize, in layers 0 to 5; 5 to 10; 10 to 20; 20 to 40 and 40 to 60 cm, in which were determined the values of pH, available soil P content, exchangeable Ca2+, Mg2+ and K+, total organic C (TOC), organic-C extracted in hot water (OC-Hw), total-N (Nt), organic-N extracted in hot water (NO-Hw), hot KCl-N (NKCl), NH4 +-N and NO3 --N. The cover crops did not cause variation in soil acidity and soil available P and exchangeable bases. The increase in TOC and Nt was favored by the cultivation of legumes, especially velvet bean gray. Larger amounts of N in labile forms were obtained from cultivation of legumes, particularly lablab and jack bean. The millet did not result in improvement of soil chemical attributes, even after twelve years of cultivation in corn pre-cropping